TESTING THE SYSTEM DESIGN OF MOTOR VEHICLE REGISTRATION PROGRAM WITH VISUAL BASIC SERVICES BUREAU ON 6.0 "XYZ" - Conny Francis; Aqwam Rosadi Kardian, Skom.,MM. (Jurnal Sistem Informasi, 2003)
In this writing, the author tries to explain about the Motor Vehicle Examination RegistrationSystem on one service bureau that is "XYZ". Confusion in making the report user dataservices, and payment for the purchase of services result in losses for the business manager(leader), this is because the work still done manually.To the authors proposed a manual system is poured into a computerized system withprogramVisual Basic 6.0, is thus expected to result from this computerized system willmembantupihak service bureau within the services sector and to create customer reports andfinancial statements are accurate and fast.